Improving Emotion Regulation Through Real-Time Neurofeedback Training on the Right Dorsolateral Prefrontal Cortex: Evidence From Behavioral and Brain Network Analyses - Yu, Linlin; Long, Quanshan; Tang, Yancheng; Yin, Shouhang; Chen, Zijun; Zhu, Chaozhe; Chen, Antao (Frontiers in Human Neuroscience, 2021)
We investigated if emotion regulation can be improved through self-regulation training on non-emotional brain regions, and the brain networks implicated in this process how to change. During the training period, the participants were instructed to up-regulated their right dorsolateral prefrontal cortex (rDLPFC) activity according to real-time functional near-infrared spectroscopy (fNIRS) neurofeedback signals, and there was no emotional element. The results showed that the training significantly increased emotion regulation, resting-state functional connectivity (rsFC) within the emotion regulation network (ERN) and frontoparietal network (FPN), and rsFC between the ERN and amygdala; however, training did not influence the rsFC between the FPN and the amygdala. Although, self-regulation training on rDLPFC significantly improved emotion regulation and generally increased the rsFCs within the networks, the rsFC between the ERN and amygdala was selectively increased. The present study also described a safe approach that may improve emotion regulation through self-regulation training on non-emotional brain regions.